Lack of efficacy of standard doses of ivermectin in severe COVID-19 patients. - Daniel Camprubí; Alex Almuedo-Riera; Helena Martí-Soler; Alex Soriano; Juan Carlos Hurtado; Carme Subirà; Berta Grau-Pujol; Alejandro Krolewiecki; Jose Muñoz (PLoS ONE, 2020)
Ivermectin has recently shown efficacy against SARS-CoV-2 in-vitro. We retrospectively reviewed severe COVID-19 patients receiving standard doses of ivermectin and we compared clinical and microbiological outcomes with a similar group of patients not receiving ivermectin. No differences were found between groups. We recommend the evaluation of high-doses of ivermectin in randomized trials against SARS-CoV-2.